PERANCANGAN SISTEM INFORMASI AKADEMIK BERBASIS MULTIUSER PADA POLITEKNIK TRI MITRA KARYA MANDIRI (TMKM) - Eko Agus Darmadi (Magister Manajemen Institut Bisnis Nusantara, 2019)
Every college, both private and public, is required to be able to adjust the development of computerized technology in order to obtain fast and accurate information as well as the Polytechnic TMKM college located at Jl. By Pass Jomin is an object in the district of Karawang. A college can never be separated from its academic role to facilitate an administrative activity in the college, the academic section at the TMKM Polytechnic College in conducting data processing activities for prospective new students has used a computerized system that is carried out only by one user who has or processing such data, however, the data produced or obtained is still inaccurate and lacks efficiency in the management or creation of such records.From the problems above, the writer will create a system that is able to overcome these problems. And therefore in solving the problem the system that will be used in designing an information system for the scope of the academic field of TMKM Polytechnic in the process of making data or managing acceptance data for prospective new students using Microsoft Visual Basic 6.0 and Microsoft SGL 2000 as a database multiuser based because using an information system that uses multiuser will be more effective because more than one user in managing the data and if there is missing data can be found because all users have the data besides saving more time and effort needed by the TMKM academic section.